PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS MACROMEDIA FLASH 8 MATERI SISTEM PERNAPASAN MANUSIA UNTUK SISWA KELAS V SEKOLAH DASAR - Salsabela, Qonita; Sahari, Sutrisno; Hunaifi, Abdul Aziz (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Based on the results of observations at Mojoroto 3 Elementary School, the implementation of science learning on the human respiratory system material has not used learning media and only uses textbooks, resulting in low interest in learning, motivation, and student learning outcomes. This is not in accordance with science learning on the human respiratory system material, because in this material, an understanding of the concept of the process and evidence is required for students to learn, namely it must be accompanied by images, animations, videos, audio, etc. This is the background for the development of macromedia flash 8 learning media on the human respiratory system material for grade V of elementary school. The objectives of this study are as follows: 1) to determine the validity of macromedia flash 8-based learning media on the human respiratory system material for grade V of elementary school, 2) to determine the effectiveness of macromedia flash 8-based learning media on the human respiratory system material for grade V of elementary school, 3) to determine the response of teachers and students to macromedia flash 8-based learning media on the human respiratory system material for grade V of elementary school. The method used is R & D (Research and Development) development. The development model is ADDIE. Data collection techniques use questionnaires and tests, data analysis uses quantitative and qualitative. The results of this development research are as follows: 1) the social science learning media for the human respiratory system material is valid because it reaches a media validity percentage of 86.90% and a teaching material validity of 94.4%. So that the final validity accumulation of both is 90.65%, 2) the learning media is effective for students based on the results of the limited trial evaluation with a percentage of completion of 80% of students, classically completed (100%), and a broad trial of 83% of students, classically completed (100%), 3) the teacher's response to the learning media is very good with a percentage of 92.5%, while the student response gets a percentage of 90% in the limited trial and 92% in the broad trial, so the learning media can be said to be practical. Based on these results, it can be concluded that this learning media is stated to be very valid and suitable for use in social science learning on the human respiratory system.